The time variable in the Territorial Digital Twin: The case of Guadalajara (Spain) - Juan Luis Bermúdez González; Enrique Castaño Perea; Enrique José Fernández Tapia (Vitruvio: International Journal of Architectural Technology and Sustainability)
The growing importance of Territorial Digital Twins (TDT) in the built environment is becoming increasingly apparent. The TDT can play a crucial role in helping governments make informed decisions based on a thorough understanding and interpretation of the evolution of both the physical territory and its urban, social, and economic development. This study develops the Territorial Digital Twin of Guadalajara (Spain), within the knowledge domain of urban planning and architectural and natural heritage. It allows the analysis of the evolution of the city, using the variable time, taking as origin an unpublished flight of Guadalajara from 1934. To be able to count on the widest possible time span, it is essential to recover the unpublished documentation that remains in historical archives. In this sense, aerial images have proved to be invaluable source for the recovery of historical heritage and territorial analysis. During the study, different techniques of image georectification have been combined, and a historical vector graphic base with topology has been created, plus an associated database accompanied by files with town planning and heritage information. As a result, the changes produced in the urban planning of the city are analysed and shown on the open-source website developed for the consultation of Territorial Digital Twin by all the stakeholders (collectivity, public bodies, university, investigation bodies, etc).